ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI PADA KANTOR DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI SELATAN - Muhammadin, Akhmad; Ridjal, Syamsul; Wahidah, - (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2025)
This research aims to test and analyze the factors that influence employee performance at Dinas Tenaga Kerja  dan Transmigrasi Provinsi Sulawesi Selatan Office. Data collection used primary data with questionnaire techniques whose population was obtained from Civil Servants at Dinas Tenaga Kerja  dan Transmigrasi Provinsi Sulawesi Selatan using a random sample system totaling 62 employees. The results of the questionnaire have been tested using SPSS Version 26 software with instrument testing, classic assumptions and multiple linear regression analysis. Based on the analysis results, this research proves that all hypotheses are accepted, and the significant variables are first, the Compensation variable has a positive and significant effect on Employee Performance. Second, the Work Spirit variable has a positive and significant effect on Employee Performance. Third, the Work Environment variable has a positive and significant influence on employee performance. Also, simultaneously each variable has a positive and significant influence on employee performance.This can prove that in general all variables can be accepted. Matching the Compensation, Work Morale and Work Environment variables of employees results in optimal performance and can achieve the desired goals at Dinas Tenaga Kerja  dan Transmigrasi Provinsi Sulawesi Selatan Office.